A prospective clinical trial of diathermy ablation for patients with high-grade cervical intraepithelial neoplasia from a single institution in Japan - Takeji Mitani; Iwao Kukimoto; Tetsuya Tsukamoto; Hiroyuki Nomura; Takuma Fujii (Scientific Reports, 2024)
Abstract Approximately 500,000 women are diagnosed with cervical cancer annually, with high-grade cervical intraepithelial neoplasia (CIN) estimated to be 20 times higher. The diathermy ablation is an inexpensive minimally invasive surgeries for CIN. However, little is known about the treatment outcomes. A prospective clinical trial was therefore conducted to evaluate ablation outcomes based on detailed colposcopy findings, cytology, and biopsy results over a two-year period. We enrolled CIN2 (n = 32) and CIN3 (n = 7) patients. Eligibility criteria included: aged between 29 and 49 (median: 36, mean: 36.3), visible transformation zone with high-grade lesions not entirely occupying the cervix, and histologically diagnosed with CIN2 or CIN3. Cytology and HPV genotyping were performed, and colposcopic findings were evaluated. Colposcopy-guided diathermy ablation was conducted by a certified gynecologic oncologist. The incidence of recurrent or residual disease was 5.1% (2/39, 95% confidence interval: − 0.02 to 0.12). The prevalence of HPV infection at 12 months decreased after surgery, as 67.6% (23/34, 0.52–0.83) of patients were HPV-negative. No severe adverse events were reported, while there were five pregnancies with full-term deliveries. The promising outcome was possibly due to selection of rigorous surgical indication and skilled surgical techniques. The study highlights the importance of experienced and skilled colposcopists. TrialRegistry This study was registered in the clinical trial registration system of the University hospital Medical Information Network Clinical Trials Registry (UMIN-CTR ID: UMIN000024483). Open for the trial to the public through the website: 01/11/2016. First registration of the patient: 30/01/2017.